Palladium-Catalyzed Regioselective Heck–Suzuki–Miyaura Cascade Cyclization for the Synthesis of Trisubstituted Arylideneisoquinolinones - Asgari, M. S.; Mirzazadeh, R.; Larijani, B.; Rashidi Ranjbar, P.; Rahimi, R.; Mahdavi, M. (Synlett, 2019)
An Ugi four-component reaction was used to construct propargylamide starting materials for a subsequent domino Heck–Suzuki–Miyaura cross-coupling reaction to give derivatives of 4-benzylidene-1-oxo-3,4-dihydro-1H-isoquinoline.
Keywords: Ugi reaction; multicomponent reactions; propargylamides; domino reaction; Heck–Suzuki–Miyaura reaction; isoquinolinones